Specific [3H]phencyclidine binding in rat central nervous system. - Zukin, S R (1979)
[3H]Phencyclidine (PCP) bound specifically and with high affinity (Kd = 0.15 microM at pH 7.4) to a single saturable class of binding sites in rat brain membrane preparations. Specific binding constituted approximately 70% of total binding at 0 degrees C and 33% of total binding at 37 degrees C (at 10 nM [3H]PCP). Bound [3H]PCP could be displaced by nonradioactive PCP, a series of its derivatives, and the psychotomimetic opiate N-allylnorcyclazocine (SKF 10,047) with relative potencies that closely paralleled those determined in animal behavioral tests. Muscarinic cholinergic ligands inhibited [3H]PCP binding, but only at 0.1 mM and in rank order at variance with that for binding to muscarinic sites or for pharmacological potencies. Other drugs, including opiates other than SKF 10,047, were unable to displace specifically bound [3H]PCP at 0.1 mM. [3H]PCP binding was most enriched in crude synaptosomal subcellular fractions, and was about three times higher in hippocampus (region of highest density) than in cervical spinal cord (region of lowest density). Trypsin and Pronase reduced specific [3H]PCP binding. Thus, PCP may exert its effects on the central nervous system via binding to specific brain receptor sites.